2017
DOI: 10.1016/j.jcp.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

A stabilized finite element formulation for liquid shells and its application to lipid bilayers

Abstract: This paper presents a new finite element (FE) formulation for liquid shells that is based on an explicit, 3D surface discretization using C 1 -continuous finite elements constructed from NURBS interpolation. Both displacement-based and mixed displacement/pressure FE formulations are proposed. The latter is needed for area-incompressible material behavior, where penalty-type regularizations can lead to misleading results. In order to obtain quasi-static solutions for liquid shells devoid of shear stiffness, sev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 62 publications
(83 citation statements)
references
References 66 publications
(196 reference statements)
1
82
0
Order By: Relevance
“…On the one hand, for a time-evolution problem such as the last example, the matrices can be computed at the beginning of the simulation and used during the whole dynamicsOn the other hand, in all problems considered here, we have found that, for relatively large meshes, the computational time required for solving the system of equations (either with an iterative solver such as GMRES with domain decomposition or with a parallel direct solver such as MUMPS) is always larger than the time required to assemble the matrix. The LMP method can be used to discretize the models in [8,9,10,12] involving vector-and tensor-valued PDEs coupled to surface evolution laws. On a time-evolving surface, Γ t , an extension of the method should provide an algorithm to evolve the local parametrization around each node.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, for a time-evolution problem such as the last example, the matrices can be computed at the beginning of the simulation and used during the whole dynamicsOn the other hand, in all problems considered here, we have found that, for relatively large meshes, the computational time required for solving the system of equations (either with an iterative solver such as GMRES with domain decomposition or with a parallel direct solver such as MUMPS) is always larger than the time required to assemble the matrix. The LMP method can be used to discretize the models in [8,9,10,12] involving vector-and tensor-valued PDEs coupled to surface evolution laws. On a time-evolving surface, Γ t , an extension of the method should provide an algorithm to evolve the local parametrization around each node.…”
Section: Discussionmentioning
confidence: 99%
“…with κ B being the bending modulus, H denoting the local mean curvature, H 0 the spontaneous curvature, κ K the Gaussian modulus and K the Gaussian curvature. On the one hand, from a given energy functional, in-plane surface stresses and moments can be deduced by functional derivatives with respect to the strain tensor [74,87] and curvature tensor, respectively [78,91,92]. On the other hand, in numerical algorithms the explicit introduction of stresses is typically bypassed and forces on the nodes discretizing the membrane are often computed directly by deriving a discretized version of the energy functional, here equations (7) and (8), with respect to the node positions [50,78,93].…”
Section: Physical Modelmentioning
confidence: 99%
“…The theory and its application example presented here provide a rigorous basis for the development of numerical methods, for example in the framework of finite elements, that are applicable to both solidand fluid-like material behavior. This is currently being considered in the framework of C 1 -continuous surface discretizations [20,18].…”
Section: Unconstrained Liquid Shellmentioning
confidence: 99%